PENGARUH SET KESEMPATAN INVESTASI TERHADAP HUBUNGAN ANTARA ASIMETRI INFORMASI DAN TINGKAT MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ni Made Suwitri Parwati; Arya Pribadi (Universitas Bunda Mulia, 2017)
This research aims to find out (a) the influence of information asymmetry on the management level directly profit (b) Influence the investment opportunity set the proxy as the opportunity to grow towards the relationship between asymmetric information and the level of earnings management. The Data used in this study is secondary data in the form of annual financial reports as well as other data related to the research. Withdrawal methods are purposive samples sampling total sample, with as many as 27 firms with a three-year research period (2008-2010). Methods of analysis used in this study is a Simple linear regression and Moderating Regression Analysis (MRA). Results of the study are (1) effect significantly or the existence of a positive relationship between Earnings Management and Information Asymmetry, (2) the investment Opportunity Set is not moderating variables (no effect) to the relationship between Earnings Management and Information Asymmetry.Keyword : Investment Opportunity Set, the asymmetry of information and the level of Earnings Management